Kedudukan Hukum Perma Nomor 2 Tahun 2012 dalam Mengefektivkan Pidana Denda pada Perkara Pencurian Ringan - Bambang Karsono (KRTHA BHAYANGKARA, 2023)
The story of grandmother Minah who was tried for stealing three cocoa beans, or Basar and Kholil who were brought to trial for stealing a watermelon and a child with the initials AP (age 13) who was charged with stealing a bucket rope is a case of theft with a relatively small economic loss. Conditions at the same time became a contrast, when corruptors stealing large amounts of state money were only given too light sentences. Supreme Court Regulation of the Republic of Indonesia number 2 of 2012 addresses the discrepancy between the limitations of minor crimes and the amount of fines in the Criminal Code with the development of the dynamics of a society whose sense of justice is disturbed and various statutory regulations are no longer according to law in society. This normative juridical research aims to determine the capacity of PERMA No. 2 of 2012 in the legal hierarchies under the Criminal Code, especially in the criminal case of petty theft. Research findings in terms of effectiveness, fines are less effective when compared to prison sentences, especially in terms of the deterrent effect on convicts, because fines can be paid by other people.